A comparison in the learning outcomes of weightlifting among students - some faculties of physical education in the Kurdistan region of Iraq - Salih, Nawzheen (Journal of Physical Education, 2023)
The research aims to identify the level of some learning outcomes (trends, cognitive achievement, skill performance) For weightlifting, we have students after the faculties of physical education and sports sciences in the Kurdistan region of Iraq, and knowledge of the differences in learning outcomes (trends, cognitive achievement, skill performance, and weightlifting among students of some faculties of physical education in the Kurdistan region of Iraq. The researcher used the descriptive approach in the method of causal comparison to suit it with the nature of the research problem The researcher used a number of means to collect information and tools Identified a community for research students of the second academic year in the faculties of physical education universities (Sulaymaniyah, Halabja, Turmian) numbering (125) students. As for the research sample, their number reached (98) students, and conducted exploratory experiments for the research variables, after determining their own standards and conducting the main experiment, and after obtaining the data, the electronic statistical bag system was used to process the data, The researcher reached the following conclusions: After processing the data statistically, the researcher concluded the following: - (The attitudes of students of the Faculty of Physical Education and Sports Sciences to the universities of (Sulaymaniyah, Garmian, Halabja) towards a weightlifting lesson were positive - The cognitive achievement of students of the Faculty of Physical Education and Sports Sciences at the university included in the research was good - The level of the members of the research sample and the three colleges was good in the skill performance of my elevation (netter and kidnapping) - The absence of significant differences for the research variables (trends, cognitive achievement, performance tasks) between the individuals and the research sample and the three samples